2003
DOI: 10.1074/jbc.m208513200
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-sensitive Lipase Is a Cholesterol Esterase of the Intestinal Mucosa

Abstract: The identity of the enzymes responsible for lipase and cholesterol esterase activities in the small intestinal mucosa is not known. Because hormone-sensitive lipase (HSL) catalyzes the hydrolysis of acylglycerols and cholesteryl esters, we sought to determine whether HSL could be involved. HSL mRNA and protein were detected in all segments of the small intestine by Northern and Western blot analyses, respectively. Immunocytochemistry experiments revealed that HSL was expressed in the differentiated enterocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…The isoform presented here is encoded by exon A, in addition to exons 1-9. Exon A is located ϳ13 kb upstream of exon 1 and has previously been shown to be incorporated in HSL transcripts in adipocytes from both hu- man and mouse (19,20) and enterocytes in mouse (11). In addition to the stated exons, there are several other exons in the region upstream of exon 1 in the HSL gene.…”
Section: Fig 2 Detection Of Hsl Exon a In Transcripts From Rat Tissmentioning
confidence: 99%
See 2 more Smart Citations
“…The isoform presented here is encoded by exon A, in addition to exons 1-9. Exon A is located ϳ13 kb upstream of exon 1 and has previously been shown to be incorporated in HSL transcripts in adipocytes from both hu- man and mouse (19,20) and enterocytes in mouse (11). In addition to the stated exons, there are several other exons in the region upstream of exon 1 in the HSL gene.…”
Section: Fig 2 Detection Of Hsl Exon a In Transcripts From Rat Tissmentioning
confidence: 99%
“…HSL has a broad substrate specificity, being able to hydrolyze, among others, mono-, di-, and triglycerides and cholesteryl esters. Besides ␤-cells and adipocytes, HSL is also present in testis, ovary, adrenal gland, heart, skeletal muscle (9), macrophages (10), and gastrointestinal tract mucosa (11). The HSL gene is located on chromosome 19 (human) (12) and spans 27 kb (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LIPE is an intracellular neutral lipase that catalyzes the hydrolysis of triacylglycerol, diacylglycerol, monoacylglycerol, and CE as well as other lipids. Although LIPE was initially identified as an adipose-specific lipase 12) , it has since been shown that LIPE is expressed in a wide variety of organs and cells, including the heart, skeletal muscle, adrenal glands, testes, ovaries, pancreatic -cells, liver, intestine and macrophages [13][14][15][16] . However, phenotypic analyses of Lipe-deficient mice generated by several laboratories, including ours, have suggested the redundancy of lipases in macrophages as well as in adipose tissue.…”
Section: Candidate Genes For Nceh Activity In Macrophagesmentioning
confidence: 99%
“…[6] HSL gene and protein structure are varying size from 88 to 130 kDa, generated by the same gene with different promoters in various tissue. [7][8][9][10] HSL in adipocyte is made up of catalytic domain in the position of N-terminal and C-terminal which is similar to all isoform of HSL. Amino acid residue such as Ser, Asp, and His present in catalytic domain and also it is phosphorylated site with its regulation.…”
Section: Introductionmentioning
confidence: 99%